2022
DOI: 10.1111/febs.16429
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of dipeptidyl peptidase 3 in pathophysiology

Abstract: Dipeptidyl peptidase 3 (DPP3), a zinc-dependent aminopeptidase, is a highly conserved enzyme among higher animals. The enzyme cleaves dipeptides from the N-terminus of tetra-to decapeptides, thereby taking part in activation as well as degradation of signalling peptides critical in physiological and pathological processes such as blood pressure regulation, nociception, inflammation and cancer. Besides its catalytic activity, DPP3 moonlights as a regulator of the cellular oxidative stress response pathway, e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 120 publications
0
13
0
Order By: Relevance
“…The most notable DPP3 substrate is angiotensin II (Ang II), which serves as the primary effector molecule of the renin–angiotensin–aldosterone system (RAAS). The RAAS plays a vital role in regulating the cardiovascular system homeostasis, modulating blood pressure through the sympathetic system, glomerular filtration, releasing endogenous catecholamine and vasopressin, and stimulating vascular smooth muscle cells [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most notable DPP3 substrate is angiotensin II (Ang II), which serves as the primary effector molecule of the renin–angiotensin–aldosterone system (RAAS). The RAAS plays a vital role in regulating the cardiovascular system homeostasis, modulating blood pressure through the sympathetic system, glomerular filtration, releasing endogenous catecholamine and vasopressin, and stimulating vascular smooth muscle cells [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses supporting their hypotensive effects were also published [90][91][92][93]. On the other hand, orthologous proteins of the dipeptidases, aminopeptidases, dipeptidyl peptidase, and serine carboxypeptidase (Table 2) have a consolidated biological role as processing enzymes [94][95][96][97].…”
Section: Discussionmentioning
confidence: 98%
“…Despite the attention gained by Dpp3 since its discovery at the end of the 1960s [13], several aspects related to its function remain elusive [14]. For example, a poorly investigated topic is Dpp3 function in the context of bone biology, which has been addressed only recently by Menale et al, who showed that the absence of Dpp3 in the mouse model Dpp3 KO caused bone loss owing to increased osteoclast activity and impaired bone quality, particularly in female mice after ovariectomy [7].…”
Section: Discussionmentioning
confidence: 99%